Detection of Secondary Metabolites, Proximate Composition and Bioactivity of Organic Dried Spirulina (Arthrospira platensis) - Taiti, Cosimo; Di Vito, Maura; Di Mercurio, Mattia; Costantini, Lara; Merendino, Nicolò; Sanguinetti, Maurizio; Bugli, Francesca; Garzoli, Stefania (Applied sciences, 2024)
In this work, Arthrospira platensis grown in Tuscany, Italy, was investigated using different analytical approaches to characterize its volatile and non-volatile chemical composition. The results showed the presence of a high number of volatile organic compounds (VOCs) such as hydrocarbons, furans, sulfides, alkanes, aldehydes, alcohols, ketones, esters and compounds belonging to other chemical classes such as fatty acids, alcohols and sugars. Furthermore, a proximal composition analysis was also performed to determine the protein, fat, carbohydrate and ash content. Total antioxidant capacity (TAC) determined by FRAP and ABTS•+ methods (5.96 mmol TE/g DW; 5.28 mmol Fe2+E/g DW, respectively), showed good reducing power and comparable free radical scavenging activity. The antibacterial power of spirulina-based alcoholic macerate (AM) was also evaluated against Staphylococcus aureus (ATCC 29213), Escherichia coli (ATCC 25922), Pseudomonas aeruginosa (ATCC 060127853), Enterococcus faecalis (ATCC 29211), Klebsiella pneumoniae (ATCC 700603) and Candida albicans (ATCC 24433) and the obtained data have shown that it had no effect against pathogenic bacterial strains. On the contrary, at low concentrations, AM exerted a prebiotic effect on some probiotic strains such as L. casei if treated with AM concentrations ranging from 1.56% v/v and 3.12% v/v and L. rhamnosus if treated with AM concentrations lower than 0.78% v/v. In conclusion, this study highlighted how spirulina, based on the rich composition and its antioxidant and prebiotic effect, can represent a source of beneficial substances for human health.